Factors responsible for the presence and distribution of black bellied sandgrouse Pterocles orientalis in the Nature Park ``Vale do Guadiana'' - Cardoso, Ana Cristina; Poeiras, Ana Sofia; Carrapato, Carlos (ARDEOLA, 2007)
Aims: Identify factors that are responsible for the presence and distribution of black-bellied sandgrouse in the nature park of `Vale do Guadiana' so that management actions can be undertaken. Localization: Southern Portugal. Methods: Kruskal-Wallis non-parametric tests and Bailey's tests was used to analyse the preferences among biotopes, while logistic regression analysis was utilized to obtain an explanation model for species distributions during breeding and non-breeding seasons. Variables considered in the analysis included presence or absence of cattle; ground vegetation coverage, height and vertical density; tree density; bush coverage; slope exposition; stone coverage and number of stones; wind direction; habitat; soil capacity; distance to roads, drinking places and villages; and altitude. . Results: The results of biotope selection indicated that sandgrouses preferred fields of leguminous plants during both breeding and non-breeding periods and tillage during the breeding period. Montado and fallows older than two years were avoided during the non-breeding season. Cereal fields were used according to their availability. Besides not significantly, fallows were highly used. For the explanation model, six variables that explain the species distribution during the breeding season were selected: cattle presence, stony ground and distance to secondary roads had a positive effect, while vegetation cover, stone cover and distance to the drinking places had a negative effect. During the non-breeding period, the model was not adjusted to validation sample. Conclusions: It was found that the most important biotopes are leguminous cultivations and fallows with extensive pastures. Grazing can have either a positive or a negative effect on these fields, depending on cattle density. Besides the number of small dams, drinking places are still a limiting factor for this species. Dispersion of settlements and roads is also negative to sandgrouse distribution. Finally conservation implications, namely management actions such as an enlargement of leguminous fields, cattle grazing control and modifications of Territory Management Plans, are discussed.
The following values have no corresponding Zotero field: pub-location: MELQUIADAS BIENCINTO 34, E-28053 MADRID, SPAIN publisher: SOC ESPANOLA ORNITOLGIA
Keywords: habitat selection; Logistic regression; management actions; Pterocles orientalis; seasonal variation

Factors responsible for the presence and distribution of black bellied sandgrouse Pterocles orientalis in the Nature Park ``Vale do Guadiana'' - Cardoso, Ana Cristina; Poeiras, Ana Sofia; Carrapato, Carlos (ARDEOLA, 2007)
Aims: Identify factors that are responsible for the presence and distribution of black-bellied sandgrouse in the nature park of `Vale do Guadiana' so that management actions can be undertaken. Localization: Southern Portugal. Methods: Kruskal-Wallis non-parametric tests and Bailey's tests was used to analyse the preferences among biotopes, while logistic regression analysis was utilized to obtain an explanation model for species distributions during breeding and non-breeding seasons. Variables considered in the analysis included presence or absence of cattle; ground vegetation coverage, height and vertical density; tree density; bush coverage; slope exposition; stone coverage and number of stones; wind direction; habitat; soil capacity; distance to roads, drinking places and villages; and altitude. . Results: The results of biotope selection indicated that sandgrouses preferred fields of leguminous plants during both breeding and non-breeding periods and tillage during the breeding period. Montado and fallows older than two years were avoided during the non-breeding season. Cereal fields were used according to their availability. Besides not significantly, fallows were highly used. For the explanation model, six variables that explain the species distribution during the breeding season were selected: cattle presence, stony ground and distance to secondary roads had a positive effect, while vegetation cover, stone cover and distance to the drinking places had a negative effect. During the non-breeding period, the model was not adjusted to validation sample. Conclusions: It was found that the most important biotopes are leguminous cultivations and fallows with extensive pastures. Grazing can have either a positive or a negative effect on these fields, depending on cattle density. Besides the number of small dams, drinking places are still a limiting factor for this species. Dispersion of settlements and roads is also negative to sandgrouse distribution. Finally conservation implications, namely management actions such as an enlargement of leguminous fields, cattle grazing control and modifications of Territory Management Plans, are discussed.
Keywords: habitat selection; Logistic regression; management actions; Pterocles orientalis; seasonal variation